1996
DOI: 10.1007/s004030050034
|View full text |Cite
|
Sign up to set email alerts
|

Known HPV types have no association with keratoacanthomas

Abstract: Certain HPV types have been linked to the genesis and development of premalignant and malignant skin diseases. There have been several contradictory reports on the role of HPV infections in the development of keratoacanthomas (KAs). To further study the involvement of HPVs in the aetiology of KAs, we investigated paraffin-embedded specimens of 80 biopsies of KAs for the presence of HPV 1, 2, 3, 4, 5, 7, 26, 37, 38, 47 and 59 DNA by in situ hybridization (ISH) with biotinylated probes under high stringency cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…No inheritance has been reported. Human papillomavirus (HPV) has not been detected in a large series of KA [17, 18, 19], and single reports on the presence of new HPV types specific for KA [20, 21]were not confirmed. However, with the introduction of highly sensitive polymerase chain reaction and degenerate primers, DNA sequences of genital and/or cutaneous HPVs were identified in 18% of KA samples [22], some of them showing histological signs of transition towards SCC.…”
Section: Discussionmentioning
confidence: 99%
“…No inheritance has been reported. Human papillomavirus (HPV) has not been detected in a large series of KA [17, 18, 19], and single reports on the presence of new HPV types specific for KA [20, 21]were not confirmed. However, with the introduction of highly sensitive polymerase chain reaction and degenerate primers, DNA sequences of genital and/or cutaneous HPVs were identified in 18% of KA samples [22], some of them showing histological signs of transition towards SCC.…”
Section: Discussionmentioning
confidence: 99%
“…Not all SCCs are infected with HPV, with reported prevalences varying widely and depending predominantly on the detection methods 93,94 . While some studies have failed to demonstrate HPV in SCC, 95–97 most studies report HPV infections in a range of 16–54% of tumours from immunocompetent individuals. Epidemiological data on the role of betaPV in cutaneous SCC have been reviewed by the International Agency for Research on Cancer (Lyon, France), which has determined that currently there is only evidence for HPV types 5 and 8 as possible carcinogens (group 2b); 89,91 however, this evidence is limited and in the context of EV only.…”
Section: Human Papillomavirus and Squamous Cell Carcinomamentioning
confidence: 99%
“…Recently, 2 of 4 keratoacanthomas were shown to be HPV positive in a study using degenerate primers that were able to amplify a broad range of different HPV types [11]. Also using degenerate primers, Lu et al [12]found no association of known HPV types with keratoacanthomas but could identify a novel HPV-type-17-related DNA sequence in 3 specimens. In a study of skin malignancies of renal transplant recipients 8 of 12 keratoacanthomas were found to contain HPV DNA [13].…”
Section: Introductionmentioning
confidence: 99%